A Lightweight, Adhesive, Dual‐Functionalized Over‐Coating Interphase Toward Ultra‐Stable High‐Current Density Lithium Metal Anodes. Issue 1 (2nd August 2020) - Li, Shaowen; Ma, Yue; Wei, Bingqing
Abstract : Coherent manipulation of the lithium plating pattern is at the heart of the safe operation of metallic anodes in the battery technologies. In this article, a lightweight ( 0.3 mg cm −2 ), dual‐functionalized carbon spheres are anchored onto the Cu foil as the interfacial protective layer via the chelation process of the catechol groups in the polydopamine precursor and the copper foil. The dual‐functionalized carbon spheres exhibit the intriguing complementary features: Lithiophilic nitrogen dopants favor the Li + ion absorption and mitigate the nucleation barrier, while the micro/mesopore reservoir spatially homogenizes the ion flux distribution, confining the metallic propagation without dendrite‐like protrusions. The metallic anode exhibits an ultra‐stable plating/stripping process for 1400 hr with the average Coulombic efficiency of 99%. A full‐cell prototype is constructed by pairing the N‐doped carbon spheres on the bare Cu (NCS‐Cu) electrode with the high‐mass‐loading LiVPO4 F (12.5 mg cm −2 ) cathode that can deliver a high energy density of 421.2 Wh kg −1 with the highest power density of 2106 W kg −1 to promise the anode use for high‐power/energy‐dense metallic batteries. Abstract : This article reports the dual‐functionalized carbon spheres as the interfacial protective layer for the dendrite‐free Li plating process on the Cu foil via the facile chelation process between catechol groups in polydopamine (PDA) precursor and Cu foil. The lightweight anode combines the high‐power feature of the supercapacitance with the energy‐dense metallic plating process.